How resilient employees can prevent family ostracism from escalating into diminished work engagement and change-oriented organizational citizenship behavior - De Clercq, D.; Pereira, R. (International Studies of Management and Organization, 2024)
Drawing from conservation of resources theory and the work–home resources model, this research examines the hitherto overlooked but highly relevant link between employees’ experience of resource-draining family ostracism and change-oriented organizational citizenship behavior, with a specific focus on the mediating role of their work engagement and moderating role of their resilience. Tests of the research hypotheses, using survey data collected among employees who work in the construction retail industry, reveal that a core channel through which social exclusion by family members translates into diminished voluntary change efforts is that employees become less engaged with work. This intermediate role of lower work engagement is less prominent, however, among employees who have a greater ability to bounce back from challenging situations. For human resource (HR) management scholars, this study accordingly helps explain why a sense of being ignored at home may lead employees to become complacent in their change efforts: Employees exhibit less enthusiasm about work. But HR management practitioners can subdue this process to the extent that they enhance and leverage employees’ resilience levels.